IDENTIFIKASI DAN TRANSLITERASI NASKAH KUNO BUTON ABAD 18 MASEHI “MI’RATUT TAMAAMI” KARYA SYEIKH ABDUL GHANI - Agus Supriatna; Sasadara Hayunari (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
There has not been much disclosure of the archipelago's ancient manuscripts, making philological research into Archipelago manuscripts is being important, especially if the text contains important information for the Indonesian nation. Archipelago manuscript contains a lot of history, customs, culture, religious teachings that are important for national identity. In the Buton region of Southeast Sulawesi, there are many ancient manuscripts. The ancient Buton manuscript has not been widely studied. One of the ancient manuscripts of the Buton Sultanate, namely Mi'ratut Tamaami Manuscript by Sheikh Abdul Ghani. The text contains the History of the Buton Sultanate and the Buton Law. The purpose of this study was to get the Mi'ratut Tamaami text that approached the original and was clear of errors, then transliterated it into Latin letters (the original alphabet Jawi) and translated it into Indonesian. This study uses the plural manuscript research methodology. This means that researchers are trying to find the existence of each copy of the existing ancient manuscript and then look for a text that is closest to the original. Manuscripts that approach the original and avoid all kinds of errors and are supported by the authenticity of their physical form will be used as the basic text in carrying out editions or transliterations of text. The text of the edited text is then translated through a cultural translation approach (cultural translation). Keywords: transliteration, ancient manuscript, Buton, 18th Century, mi’ratut tamaammi